2017
DOI: 10.1155/2017/4842025
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Silodosin Monotherapy and the Reasons for Withdrawal from Treatment of Previously Untreated Japanese Patients with Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Hyperplasia

Abstract: Objectives The persistence of silodosin and the reasons for withdrawal from treatment of previously untreated Japanese patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia (LUTS/BPH) were evaluated in real-life clinical practice. Methods A total of 81 previously untreated Japanese patients diagnosed with LUTS/BPH were treated with silodosin monotherapy and prospectively followed for 4 years. The persistence rate was estimated using the Kaplan-Meier method. If silodosin had to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The 5-year persistency for tamsulosin is 30.4%, 7 and the 3-and 4-year rates for naftopidil are 21.4% and 19%, respectively. 8,9 In the case of silodosin, one study showed that the 4-year persistency rate was 35.8%, 10 and another that the 6-year rate was 25%. 11 According to the present prospective observational study, one of the reasons for withdrawal was unsatisfactory effects in 28.8% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year persistency for tamsulosin is 30.4%, 7 and the 3-and 4-year rates for naftopidil are 21.4% and 19%, respectively. 8,9 In the case of silodosin, one study showed that the 4-year persistency rate was 35.8%, 10 and another that the 6-year rate was 25%. 11 According to the present prospective observational study, one of the reasons for withdrawal was unsatisfactory effects in 28.8% of patients.…”
Section: Discussionmentioning
confidence: 99%